2021
DOI: 10.3390/ijerph18179162
|View full text |Cite
|
Sign up to set email alerts
|

Is Dry Needling of the Supinator a Safe Procedure? A Potential Treatment for Lateral Epicondylalgia or Radial Tunnel Syndrome. A Cadaveric Study

Abstract: The supinator muscle is involved in two pain conditions of the forearm and wrist: lateral epicondylalgia and radial tunnel syndrome. Its close anatomical relationship with the radial nerve at the arcade of Frohse encourages research on dry needling approaches. Our aim was to determine if a solid filiform needle safely penetrates the supinator muscle during the clinical application of dry needling. Needle insertion of the supinator muscle was conducted in ten cryopreserved forearm specimens with a 30 × 0.32 mm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…The distances observed in the current study during the US-guided intervention were higher than those reported in this previous study [ 16 ], supporting the potential improved safety of the procedure if US-guided. Additionally, the cadaveric study also revealed that the tip of the needle reached the radius bone in 80% of the specimens [ 16 ]. The application of US imaging allowed hitting the bone with the needle to be avoided in the current study.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…The distances observed in the current study during the US-guided intervention were higher than those reported in this previous study [ 16 ], supporting the potential improved safety of the procedure if US-guided. Additionally, the cadaveric study also revealed that the tip of the needle reached the radius bone in 80% of the specimens [ 16 ]. The application of US imaging allowed hitting the bone with the needle to be avoided in the current study.…”
Section: Discussionsupporting
confidence: 63%
“…This study found that needling insertion of the supinator muscle at Frohse arcade with both approaches provided enough space to avoid penetration of the neurovascular bundle, particularly if the procedure was US-guided. A recent cadaveric study reported distances of 8 mm from the tip of the needle to the different branches of the radial nerve during the application of dry needling with the forearm in pronation [ 16 ]. The distances observed in the current study during the US-guided intervention were higher than those reported in this previous study [ 16 ], supporting the potential improved safety of the procedure if US-guided.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation